Process for Making Shafts for Locking Saws - Fachri Rizieq Ramadhan; Marno Marno (Journal of Education Technology Information Social Sciences and Health, 2024)
The process of making a saw locking shaft is a crucial step in ensuring the reliability and safety of the saw machine. The crux of the problem at hand is the need for a locking shaft with sufficient strength and resistance to secure the saw blade in position during operation. The aim of this research is to design and produce saw locking shafts using a lathe and milling machine. This research was carried out in a local lathe workshop, which has facilities for turning and milling processes. The method used in this research was experimental using ST 37 steel as the basic material. The manufacturing process involves a turning stage to achieve the desired dimensions and a milling stage to ensure conformity to shape and tolerance. The research results show that the resulting saw locking shaft has the right dimensions and a smooth surface. The conclusion of this research is that the saw locking shaft made using ST 37 steel through conventional turning and milling processes succeeded in meeting the expected specifications. This success shows the effectiveness of the method used and provides a solid basis for the production of saw locking shafts on a larger scale.